Associação entre o consumo de alimentos ultraprocessados e indicadores de obesidade no ELSA-Brasil (2008-2010) - Fernanda Marcelina Silva (2017)
Obesity is an epidemic disease resulted from a complex and multifactorial process defined by abnormal or excessive fat accumulation in adipose tissue in result of a positive energy balance and with serious consequences to health. A rise in global obesity rates over the last decades has been substantial and affects most countries. Production and consumption of ultra-processed food have risen in parallel with the increase in obesity. Ultra-processed foods are formulations made by the food industry mostly from substances extracted from foods or obtained from processing of constituents of foods or through chemical synthesis. These formulations are higher in energy density, contain greater levels of added sugar, sodium, total, saturated, and trans fats and are lower in dietary fiber and micronutrients. Also, they are very durable, palatable and convenient. The aim of this study was to verify if the intake of ultraprocessed foods is associated with higher body mass index and waist circumference among participants from the baseline of the Longitudinal Study of Adult Health (ELSA-Brasil) (2008-2010). The ELSA-Brasil cohort consists of 15105 public servants (35-74 years old) of higher education and research institutions in six Brazilian states. This study is a cross-sectional analysis of 8977 participants aged 35 to 64 years old. The percentage energy contributionof ultra-processed foods in total energy intake was the explanatory variable, grouped in quartiles for the analysis. Body Mass Index (BMI) and Waist circumference (WC) and their respective cut-off points served as response variables (continuous and categorical). Linear and multinomial regressions were used to evaluate the relationship between the comsumption of ultra-processed foods and BMI and WC controlling for sociodemographic characteristics, socioeconomic indicators, health-related behaviors, and comorbidities. Ultra-processed foods contributed with 22.7% of the total caloric intake. After adjustments, individuals in the last quartile of ultra-processed food intake presented a higher BMI (=0.80 kg/m²; 95% CI=0.53; 1.07) and WC (=1.71; 95% CI=1.02; 2.40), and higher chances of being overweight (OR=1.31; 95% CI=1.13; 1.51), obese (OR=1.41; 95% CI=1.18; 1.69) and presenting a significantly increased WC (OR=1.41; 95% CI=1.20; 1.66) in comparison to those in the first quartile. These associations showed a clear upward dose-response gradient. The results of the present study suggest that the intake of utraprocessed food, independent of the amount of total caloric intake, is associated with greater BMI and WC after adjustments for covariates. Our findings support the hypothesis that link the increase in consumption of ultra-processed food worldwide to the obesity epidemics. They also reinforce the need of public policies aimed to reduce the intake of ultra-processed foods.